Epidemiological and bacteriological profile of neonatal bacterial infections seen in hospital pediatric in Antananarivo - Rabevazaha, Ny Ando A.; Rahajamanana, Vonintsoa L.; Andriatahina, Todisoa N.; Rakotojoelimaria, Elsa H.; Ranivoson, Andrianina H.; Robinson, Annick L. (International Journal of Research in Medical Sciences, 2019)
Background: Neonatal bacterial infection is one of the leading causes of new-born morbidity and mortality. Bacterial ecology is not known in our unit, no study has been devoted to this subject. This work aimed to determine the germs responsible for neonatal bacterial infections and their level of sensitivity to the usual antibiotics. Methods: This is a retrospective descriptive study conducted in the Neonatology Department from January 1, 2018 to April 30, 2019 (16 months) including all newborns under 29 days hospitalized during the study period and possessing positive bacteriological results regardless of the site of collection (blood, urine, cerebrospinal fluid). Results: The diagnosis of neonatal infection was confirmed in 47 cases, i.e. 26.1% of suspicions of neonatal bacterial infection hospitalized during the study period. The female predominance was found with a sex ratio of 0.81. The most frequently isolated germs are, in order of frequency, coagulase-negative staphylococci (10 cases), Escherichia coli (7 cases), Enterobacter cloacae (5 cases), Klebsiella pneumoniae (5 cases) and Enterobacter aerogenes (5 cases). Of the 47 cases studied, 16 cases were multidrug-resistant infections including 7 cases i.e. 14.9% of nosocomial infections. The majority of Enterobacteria are strains producing broad spectrum beta lactamases (12 cases to 22). The molecules that remained effective were mainly Imipenem and Amikacin. Conclusions: Neonatal infection remains a real public health problem. The emergence of multi-resistant bacteria complicates the management. The knowledge of bacterial ecology on a wider population is an important asset in its prevention and management.